2014
DOI: 10.1016/s0187-6236(14)71098-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hail through the three-body scattering signatures and its effects on radar algorithms observed in Romania

Abstract: RESUMENLa red de radares de la Administración Meteorológica Nacional de Rumania (NMA, por sus siglas en inglés) integra cinco radares de la banda S y cuatro radares de la banda C. La observación de procesos de convección en Rumania mediante la red de radares Doppler ofrece una nueva perspectiva para comprender el riesgo climatológico de ciertas regiones y entornos de mesoescala. Se observan mejor los sistemas convectivos altamente organizados, como las supercélulas, y su amenaza subsiguiente puede predecirse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…15b). This conclusion is based on the relationship between the Doppler radial velocities in the TBSS area, the storm core, the vertical velocities associated with hydrometeors (Zrnić, 1987;Carbunaru et al, 2010), and the presence of high positive Doppler velocity in the beginning of TBSS.…”
Section: Montana Supercellmentioning
confidence: 99%
“…15b). This conclusion is based on the relationship between the Doppler radial velocities in the TBSS area, the storm core, the vertical velocities associated with hydrometeors (Zrnić, 1987;Carbunaru et al, 2010), and the presence of high positive Doppler velocity in the beginning of TBSS.…”
Section: Montana Supercellmentioning
confidence: 99%
“…In Romania, there are only a few studies that have investigated convective events, and such studies examined severe convective storms and tornadoes [23][24][25]. Manea et al [17] have found statistically significant increasing trends in the frequency of days with rain showers and snow showers over most of Eastern Romania, with no statistically significant trends in the frequency of sleet showers.…”
Section: Introductionmentioning
confidence: 99%
“…Radar reflectivity can be used to assess and monitor the intensity of precipitation and to infer the precipitation type. The occurrence of hail on the ground that causes severe damage is very likely when the radar reflectivity exceeds a threshold of 55 dBZ (Sandu et al 2010;Schiesser 1990;Schuster et al 2006;Carbunaru et al 2014;Junghänel et al 2016). However, vegetation damage can be estimated based on multispectral images.…”
Section: Introductionmentioning
confidence: 99%